The Impact of Leadership and Communication on Safety Culture Maturity Level - Natasya Andelia; Gerry Silaban; Isyatun Mardhiyah Syahri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Safety culture is the way workers behave safely when working without supervision. In addition, five levels categorized into pathological, reactive, calculative, proactive, and generative levels are used to evaluate the level of safety culture maturity. This research aims to determine the influence of leadership and communication on the level of maturity of safety culture at the State Electricity Company Project Management Center-Construction Management Implementation Unit IV. The type of research used in this research is quantitative research with a cross sectional research design. The research will be carried out at the limited liability company national electricity company project management center-construction management implementation unit IV which operates in the field of construction management services. The research was conducted from March to August 2023. The sample collection technique was total sampling. The research sample was 71 respondents. The research instrument used was a questionnaire. Data analysis using SEM-PLS or Partial Least Square- Structural Equation Modeling analysis using SmartPLS software. The research results show that leadership has a significant effect on the level of safety culture maturity (p value < 0.05), and communication has a significant effect on the level of safety culture maturity (p value < 0.05). Leadership and communication simultaneously have a significant influence on the level of safety culture maturity, with a combined contribution of 70.7% from these two variables. Meanwhile, the rest is influenced by other variables not examined in this research. Keyword: Communication, Leadership, Safety culture maturity level